Oficina de linguagem na saúde da família: um dispositivo de cuidado e promoção à saúde - Ribeiro, Allyne (2012)
Introduction: This study proposes a reflection on the demands of clinical speech: concerns and anxieties of patients who face problems with reading and writing. Through Language Workshop, we investigated and dealt with the writing demands of patients treated by a team from the Family Health Strategy (FHS), from the idea that writing practices must be meaningful to the patients, as well as socially contextualized . Objective: The aim of this work was to collect and investigate the potential of the Language Workshop as a care device and health promoter in primary care. Method: research intervention, carried out through the Language Workshop sessions, which were mediated by situations and scenarios constructed by the research patients and the researcher. These activities were supported by theoretical formulations of reference. Results and Discussion: The Language Workshop, in addition to promoting the understanding and the displacement of the patient without regard to their anxieties and concerns with reading and writing, pointed to the fact that such a device, putting at stake the dimensions of everyday life and history people and families in a given community, promotes literacy processes, and facilitates learning of formal writing. In this sense and in certain ways, the capability of the Language Workshop is in the process of intensive construction, singularization and analysis of clinical events experienced collectively in the case through genres of written language. Conclusion: The Language Workshop, as a medical device to promote health care, allowed to investigate and deal with written demands of patients, and promoted social and emotional movement, expanding the possibilities for overcoming reading and writing disorders shown